Re-evaluation on assumptions in Islamic economics: a preliminary study - Muhammad, Mohd Zulkifli; Abdullah, Azwan (Universiti Teknologi MARA, Kelantan, 2018)
This paper is intended for a preliminary study in re-evaluating Islamic economics assumptions. The assumptions were based on the two common assumptions in economic system which includes scarcity of resources and humans unlimited wants. This paper analyses how far these assumptions in Islamic economics placed tawheed as their axis and aligned with tasawwur Islam. The analysis was done by studying opinions and views of several Islamic economists. Content analysis and literature review were utilized to reach this objective. From this preliminary study, it was found that the current assumptions in Islamic economics were not favouring towards the true concept of tawheed and tasawwur Islam. It implies the needs for a more comprehensive study to be done in order to come up with a new resolution on the real assumptions of Islamic economics